Sense of life and mental health - Zamudio Flores, David Alberto (2021)
This essay addresses the importance and significance of the conception of the meaning of life and its subsequent enrichment throughout a person's life, as well as its implication in a therapeutic process, all as an essential part of strengthening health mental. Reflection and analysis of the author from the review of bibliographic sources in a methodical and systematic way, articles, research reports and scientific psychology journals indexed in electronic databases, as well as, the use of physical and digital books. Having a healthy, inspiring and intrinsic sense of life allows strengthening the foundations of mental health, as well as contributing significantly to the entire therapeutic process, exercising prevention and timely intervention.